The inflammatory endotype in osteoarthritis: Reflections from the 2024 OARSI clinical trials symposium (CTS) with a special emphasis on feasibility for clinical developmentBiomarkers of high value - Morten Asser Karsdal; Lucio C. Rovati; Jeyanesh Tambiah; Olga Kubassova; Christoph Ladel; Francis Berenbaum; Anne-Christine Bay-Jensen; Lachy Mclean; Richard Loeser; Ali Mobasheri; Virginia B. Kraus (Osteoarthritis and Cartilage Open)
Objective: The inflammatory endotype is arguably one of the most well-established endotype in osteoarthritis (OA). While endotyping holds promise for advancing drug development, numerous potential challenges must be considered, addressed and resolved before successful clinical outcomes can be achieved. Design: Since 2017, the Osteoarthritis Research Society International (OARSI) has hosted the Clinical Trials Symposium (CTS). Each year, OARSI and the CTS steering committee encourage discussions on selected topics among a broad range of stakeholders, including regulators, drug developers, clinicians, clinical researchers, biomarker specialists, and basic scientists, with the aim of advancing drug development in the OA field. Results: This report highlights the ongoing tension between academia's “blue ocean” strategy and the feasibility-driven approach of drug developers, all within the context of scientific efforts to find effective solutions. Understanding the needs, goals, constraints, and opportunities of all involved stakeholders is crucial for defining optimal drug development strategies for OA. Conclusion: A multidisciplinary, collaborative approach is essential for developing effective OA treatments, balancing scientific discovery with regulatory and clinical feasibility.